The Indian health and demographic surveillance system network: Opportunity to generate evidence for public health policy - Arun K Yadav; Rutuja Patil; Sanjay Juvekar (Wolters Kluwer Medknow Publications, 2023)
The Health and Demographic Surveillance System (HDSS) is a valuable longitudinal cohort study that tracks the health and demographic changes of a geographically defined population, serving as a platform for research and evidence-based policymaking. In India, there are nearly 20 HDSS sites covering diverse areas and populations totaling around two million. To foster collaboration, the Indian HDSS Network (IHN) was formed, comprising 19 sites from 16 institutes, covering a population of 1.5 million. The IHN aims to standardize data collection processes while allowing site-specific autonomy, generating high-quality longitudinal health, and demographic data. To ensure effective coordination, a governance structure with a rotating secretariat and working committee was proposed. The IHN envisions conducting robust multicentric research, supporting data-driven efforts to improve population health, and promoting research-policy synergy. The network's outcomes have the potential to optimize health research funding, generate epidemiological data, and provide evidence for public health policy. Collaboration within the IHN strengthens HDSS sites in newer technologies and community-based research, fostering capacity building. Seed funding is being sought to formalize and support the day-to-day functioning of the network, which holds promise for advancing population health and informing policymaking in India.